2015
DOI: 10.5539/ass.v11n25p101
|View full text |Cite
|
Sign up to set email alerts
|

Rural Banking in Ghana and Its Impact on Rural Farmers. Case Study of the Birim South District, Ghana

Abstract: This study examines the impact of financial institutions, especially rural banks on rural farmers. It analyses the role rural banks play in agricultural development and food security of the Birim South District in the Eastern Region of Ghana.The aim of the research was to (1) evaluate the rationale of the introduction of rural banks in Ghana and their impact on the rural folks (especially farmers) (2) establish a link between rural banking and food security (3) understand constraints farmers face in their deal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In Figure 1, show simulated profitability SDE model performance of RCB's over the period to assess the trend of company's ability to earn profits from its sales or operations, balance sheet assets, or shareholders' equity. The series however exhibited cyclic movements which are cycles of rising and falling from initial time point zero (0) to one (1), data values that do not repeat at regular intervals. Such oscillatory movements of time series often have the duration of more than a Business Cycle.…”
Section: Model Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 1, show simulated profitability SDE model performance of RCB's over the period to assess the trend of company's ability to earn profits from its sales or operations, balance sheet assets, or shareholders' equity. The series however exhibited cyclic movements which are cycles of rising and falling from initial time point zero (0) to one (1), data values that do not repeat at regular intervals. Such oscillatory movements of time series often have the duration of more than a Business Cycle.…”
Section: Model Simulationmentioning
confidence: 99%
“…Banks serve as financial intermediaries that accept deposits from customers and use them in the form of loan facilities to deficit spending units in the economy [1] In Ghana, the business of banking remains one of the most lucrative industries despite increasing competition and in the attempt to remain competitive; banks are exposed to several factors which can affect their profitability [2]. One of the key players in the Ghanaian banking industry is the Rural and Community Banks (RCBs) to fast track the development of rural areas of Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…The result of the study revealed that major limitations or challenges in accessing agricultural credit as found in the report include; high interest rates, bureaucratic bottlenecks, late approval of loans, unnecessary request for guarantors and collateral. Also, Afful et al (2015) examined the impact of financial institutions, especially rural banks on rural farmers. The result showed that farmers in the area enjoy the services of the bank and the bank itself has made significant impact on their lives not just only through the disbursement of credit or as something to fall back on when their income source is low but that it has had a high effect on output, income, savings and labour force.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many publications focused on either the regional context of the country in addressing the significance of rural banks while others focused on the crop subsector at large. For instance, Kadri, and Afful et al [10,11] evaluated the importance of rural banks in Ghana and come to a conclusion that the agriculture sector was deprived of working capital as compared to the other sub-sectors of the economy. The limitation of these studies is their inability to identify an export earning crop and point out the importance of rural credit in its productivity.…”
Section: Introductionmentioning
confidence: 99%